From shamanism to Sufism : women, Islam and culture in Central Asia - Sultanova, Razia (London ; New York : I.B. Tauris, 2014)
Women have traditionally played a vital part in Islam throughout Central Asia -- the vast area from the Caspian Sea to Siberia. With this ground-breaking and original study, Razia Sultanova examines the experiences of Muslim women in the region and the ways in which religion has shaped their daily lives and continues to do so today. From Shamanism to Sufism explores the fundamental interplay between religious belief and the cultural heritage of music and dance and is the first book to focus particularly on the role of women. Ritual and music are at the heart of Central Asian and Islamic culture, not only at weddings and funerals but in all aspects of everyday life. Through her in-depth analysis of these facets of cultural life within Central Asian society, From Shamanism to Sufism offers important insights into the lives of the societies in the region. The role of women has often been neglected in studies of religious culture and this book fills an enormous gap, restoring women to their rightful historical and cultural context. It will be essential reading for anyone with a serious interest in the History or Religion of Central Asia or in Global Islam. -- Publisher description.
Historical overview -- Shamanism in Nomadic culture -- Sufism in Central Asia -- Female Sufism -- Transmission of sacred knowledge in its connection to Sufi tradition -- Music and female Sufis -- Interaction of Shamanism and Sufism in Central Asian female performance -- Musical instruments and dances in female communities -- Female folk Sufism -- Female rituals -- Similar female rituals in the Turkic-speaking world (in Tatar, Azeri, Turkish, Cypriot, and Afghani traditions) -- Appendix: Femal poetry.
Includes bibliographical references (page 231-238) and index.
Keywords: Women -- Asia, Central -- Social conditions; Women in Islam -- Asia, Central; Islam -- Asia, Central; Shamanism -- Asia, Central; Sufism -- Asia, Central; Asia, Central -- Social conditions